2011
DOI: 10.1021/jm200149e
|View full text |Cite
|
Sign up to set email alerts
|

Enone– and Chalcone–Chloroquinoline Hybrid Analogues: In Silico Guided Design, Synthesis, Antiplasmodial Activity, in Vitro Metabolism, and Mechanistic Studies

Abstract: Analogs of the previously reported antimalarial hybrid compounds 8b and 12 were proposed with the aim of identifying compounds with improved solubility and retained antimalarial potency. In silico characterization predicted improved solubilities of the analogs, particularly at low pH; they retained acceptable predicted permeability properties, but were predicted to be susceptible to hepatic metabolism. These analogs were synthesized and found to exhibit notable in vitro antimalarial activity. Compounds 25 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(59 citation statements)
references
References 42 publications
(98 reference statements)
5
53
0
1
Order By: Relevance
“…Overall, we can conclude that it is possible to create cinnamic acid/4-aminoquinoline conjugates with promising antimalarial and FP-inhibitory activities, at levels comparable to those of recently reported chalcone-based hybrids [46,47]. Such conjugates constitute promising leads for future development of novel antiplasmodials targeted at blood-stage malaria parasites.…”
Section: Both Families Of Compounds Studied (Hedicins 8 and Hecins 9)supporting
confidence: 74%
“…Overall, we can conclude that it is possible to create cinnamic acid/4-aminoquinoline conjugates with promising antimalarial and FP-inhibitory activities, at levels comparable to those of recently reported chalcone-based hybrids [46,47]. Such conjugates constitute promising leads for future development of novel antiplasmodials targeted at blood-stage malaria parasites.…”
Section: Both Families Of Compounds Studied (Hedicins 8 and Hecins 9)supporting
confidence: 74%
“…Some hybrid drugs, capable of targeting two processes in the malaria life cycle where one of the targets is FP2 inhibition, can fall into the category of non-peptidic small inhibitors [122,123]. For instance, in 2010, Chibale's group identified chalcone-chloroquine hybrid 40 as a promising antimalarial (Fig.…”
Section: Non-peptidic Inhibitorsmentioning
confidence: 99%
“…For instance, in 2010, Chibale's group identified chalcone-chloroquine hybrid 40 as a promising antimalarial (Fig. 30) [122,123]. Compound 40 and related hybrid structures were synthesized and showed to be active against Pf.…”
Section: Non-peptidic Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The chalcones have displayed an impressive array of pharmacological activities such as antiprotozoa [8][9][10] , anti-inflammatory 11,12 , antituberculosis agents 13 , immunomodulatory 14 , and anticancer 15 . As our research is devoted to the synthesis of diverse structures as anti-infective agents, we identified the chalcone as good anti-infectious agents [16][17][18] . Keeping this in mind, we designed and synthesized new prototypes by combining both urenyl Bis-acetophenone and substituted benzaldehyde to yield the corresponding Bis-chalcones (Scheme 1) and highlighted their in vitro and in vivo antimalarial activities.…”
Section: Introductionmentioning
confidence: 99%